Genetic variation, hybridization, in-vitro germination, and morphometric studies of wild orchids (aerides spp.) - Chalaparmal, Sivanaswari (2015)
Aerides odorata, Aerides odorata var.Yellow, Aerides quinquevulnera var. Calyana, Aerides jlabellate and Aerides houlletiana are five wild and endangered orchid species with immense floricultural traits. Comparative study using Polymerase Chain Reaction (PCR) based marker, Inter Simple Sequence Repeat (ISSR), were performed to access the genetic variation among these wild orchids. Among 15 ISSR primers tested, 14 primers showed reproducible bands. 71 bands out of75 bands were polymorphic.Aerides odorata and Aerides odorata var. Yellow with Aerides jlabellata and Aerides houlletiana were closest genetically. While, Aerides quinquevulnera var. Calyana was found to be most genetically diverse as compared to the other four species. Physical clustering of the loci present in the species were identified. These new polymorphic ISSR loci clearly delineate genetic variation and will aid in investigating the extent of gene flow taking place between species of Aerides. The intergeneric hybrids were synthesized by performing reciprocal crosses between species studied. The crosses performed were Aeride sodorata x Aerides quinquevulnera var. Calyana, Aerides odorata x Aerides jlabellata, Aerides odorata var.Yellow x Aerides quinquevulnera var. Calyana and their reciprocals. Aerides odorata x Aerides quinquevulnera var. Calyana and its reciprocal cross were the most compatible cross. Seed morphometry and scanning electron microscopic studies of four Aerides species and four hybridized seeds were presented. All the presently investigated taxa were different in their seed size, shape and colour. Seed colour ranges from pale yellow to yellow and brown. Variation between maximum and minimum in the length/width ratio of seed were discussed. Data on the seed volume showed that higher seed volume is the result of both greater length and width. Special attention was paid to study the morphology of parent and hybridized seeds and different stages of protocorms produced in vitro. Seed types were recognized according to the classification of Dressler. Gathering of these data is to provide genetic information for development of breeding strategies and conservation of endangered as well as economically important orchid species strategies. Successfully hybridized seeds of the hybridization study were subjected into in-vitro study to determine the effects of kinetin and 6-Benzylaminopurine (BAP) (0.5, 1.0, 1.5,2.0 mgIL) to their germination. In vitro germination response of the both immature hybrid embryos of Aerides odorata x Aerides quinquevulnera var. Calyana and Aerides quinquevulnera var. Calyana x Aerides odorata were found to be best on Murashige and Skoog medium supplemented with kinetin 1.5 mgIL and BAP 1.5 mgIL respectively. These two plant growth regulators with l.5mg/L concentration level also resulted in earliest growth and shortest time for shoot and root development of both hybrids.